Sosialisasi Etika Bisnis untuk Manajemen Usaha Pelaku UMKM di Lelamase - Kartin Aprianti; Hidratul Iftar; Nur Fauziah Nabila; Nurirna Sakinah; Fayzha Oktavia; Khairunnisah Khairunnisah; Fitri Wulandari (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
Doing business, big or small, is bound up with ethical issues. Ethics refers to what one should do morally. Umkm Socialization activities are MSMEs engaged in wood processing made from teak wood located in lelamase. Socialization activities have the aim of providing knowledge to umkm about business ethics that umkm need to have in doing business. plus umkm businesses are located in densely populated places. It is necessary to maintain ethical behavior where umkm businesses are located. the method offered to MSMEs is in the form of socialization using LEAFLETS which are carried out door to door. The material provided in the leaflet includes a discussion of (1) The Role of Ethics in doing business for MSME actors, (2) Benefits in doing business for MSME actors (3) Application of ethical principles in business in financial, marketing, production and HR activities. The results of the activity showed that MSMEs were very enthusiastic in listening and discussing during the activity. In addition, it can provide knowledge about ethics in running a business.